Tumor CD19 Expression Determines Distinct Clinical Outcomes After CD19 CAR T-Cell Therapy in Large B-Cell Lymphoma - Magdalena Corona; Aaron Gillmor; Kimon V. Argyropoulos; Teng Fei; Maria Isabel Sotelo-Alva; Mohammad Alhomoud; Parastoo B. Dahi; Anthony F. Daniyan; Mark T.A. Donoghue; Sigrun Einarsdottir; Lorenzo Falchi; Qi Gao; et al. (Blood Cancer Discovery, 2026)
Abstract It remains uncertain whether lower CD19 expression is clinically relevant for outcomes of CD19 CAR-T therapy of large B-cell lymphoma (LBCL). We conducted an integrative analysis of tumor CD19 levels with centralized quantitative assessment by flow cytometry (FC), immunohistochemistry and RNA-sequencing in a LBCL cohort (n=301). Pre-treatment CD19 by FC correlated with 1-year progression-free survival following axicabtagene ciloleucel or lisocabtagene maraleucel (16%, 53% and 64% for CD19low, CD19intermediate and CD19high, respectively; p=0.005). After CAR-T relapse, proportion of CD19low tumors increased (from 17% to 35%). Concordant associations were observed by immunohistochemistry and RNA-sequencing. Transcriptomic profiling linked lower CD19 to inflammatory pathways, validated in an external LBCL cohort (n=1,017). Genetic loss of the CD19 locus was observed in 8% of pre-CAR-T and 11% of post-CAR-T tumors (p=0.82), while no CD19 coding mutations were identified. Overall, CD19 expression is a clinically meaningful determinant of CAR-T outcomes, supporting quantitative assessment to improve risk stratification.